Protective Effect of an Antibody against Specific Extracellular Domain of TLR2 on Agonists-Driven Inflammatory and Allergic Response. (24th April 2016) - Guo, Tianwu; Cai, Jun; Peng, Yanxia; Zhang, Lifang; Lan, Qiaofen; Chen, Yanwen; Liao, Huanjin; Xie, Tong; Wu, Ping; Pan, Qingjun
Abstract : Specific blocking strategies of TLR2-mediated inflammatory signaling and hypersensitivity reactions may offer novel therapeutic strategies to prevent a variety of diseases. In this study, we investigated the blocking effects of a new anti-TLR2 antibody anti-T20 against a 20 mer peptide T20 located in the extracellular specific domain of mouse TLR2. In addition, the effects of the anti-T20 in vitro, measuring the inhibition of the IL-6 and TNF- α production in response to PGN, LTA, and Pam3CSK4-stimulated RAW264.7 cells, were determined. In vivo, the effects of anti-T20 on a lethal anaphylaxis model using PGN-challenged OVA allergic mice, including the rectal temperature and mortality, and serum levels of TNF- α, IL-6, and LTC4 were assayed. The results showed that anti-T20 specifically bound to TLR2 and significantly inhibited PGN, LTA, and Pam3CSK4-driven TNF- α and IL-6 production by RAW264.7 cells. Also, anti-T20 protected OVA allergic mice from PGN-induced lethal anaphylaxis, and the serum levels of TNF- α, IL-6, and LTC4 of anti-T20 treated PGN-challenged OVA allergic mice were decreased as compared to isotype control of anti-T20 treated mice. In summary, this study produced a new antibody against the specific extracellular domain of TLR2 which has protective effect on TLR2 agonists-driven inflammatory and allergic response.